Strengthening North-South Relations: The Case of EU and ECOWAS Cooperation (Global Focus, 2021)
Regional integration is discussing cooperation among states in a region and the influence of external states or organizations. The cooperation among regions is known as inter-regionalism. As a leader in regional integration, European Union (EU) has been cooperating with the other regions since their name was European Economic Community. Firstly, Europe established relations in the form of political dialogue and cooperation with ASEAN and Asian countries. For this occasion, the EU established Asia Europe Meeting (ASEM). Subsequently, the EU created external relations with African, Caribbean, Pacific (ACP), South American, etc. This research elaborates on the relation of the EU with the West African region. The Economic Community of West African States (ECOWAS) is the regional institution chosen by the EU to engage in the relationship. Some scholars acknowledged that ECOWAS is one of the most organized institutions in the African Region. Asymmetric relation between EU and ECOWAS denotes the relation of The North and The South countries. By analyzing the inter-regionalism framework, this paper exercises a liberal institutional perspective as the main paradigm. The results found that inter-regionalism could reinforce strong institutions in both regions.